IMPLIKASI ORGANISASI MAHASISWA KESATUAN AKSI MAHASISWA MUSLIM INDONESIA (KAMMI) DALAM MEMBENTUK KARAKTER MELALUI DAURAH MARHALAH I - Ahmad Bustomi (Nizham Journal of Islamic Studies, 2021)
The background of this research is the existency of extra campus organizations which have an ideology contradicting with Pancasila as the Nation Ideology and its democracy system which according to researcher it strongly threatens the integrity of Negara Kesatuan Republik Indonesia. On the other side, there are many news in various media which issues the confusions between Islamic Mission becoming the spirit of Islamic students organizations and the practice of some cadres in field such as fighting among islamic students and destroying campus or public fasilities. Absolutely recruitment curriculum is an important aspect to be analyzed more deeply considering from where it will be seen the direction of this students’ movement working, the background and spirit of organizations. Therefore, the researcher focuses on something important to be analyzed especially related to the role of islamic student organization of extra campus on the forming of students’ character of KAMMI cadre in UIN Sunan Kalijaga. The selection of organization around UIN Sunan Kalijaga is chosen because of the location in Yogyakarta, in which mostly becomes a place for the establishment of student organizations and UIN Sunan Kalijaga it self has a massive organization climate. This researchs are to describe the role of islamic student organization of extra campus in the forming of student characters by using a qualitative approach with the subject of research (informant) consisting of Leader, Secretary and Leader of Public Policy division. The metodes of data collection used are interview, observation, and documentation. Data analysis uses Milles Huberman model with data reduction technique, data presentation, and conclusion. The results of research show that: Firstly, The implementation of cadre curriculum KAMMI is as the method which has Guide in DAURAH MARHALAH called MC Instructor whose duty give introduction before presenter, guides the learning process in class and fgd/fanel companion, while the speakers is called the instructor. The method of study which consists of lecture method, question and answer, fgd/sgd, panel, group dinamics and debate. Second, the role of curriculum shows eight characters religious, tolerance, discipline, democratic, friendly/communicative, like to read, social care and responsible